1990
DOI: 10.3109/02656739009140820
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional clinical studies on hyperthermia combined with radiotherapy or chemotherapy in advanced cancer of deep-seated organs

Abstract: Multi-institutional studies on clinical hyperthermia of deep-seated tumours were undertaken using 8 MHz radiofrequency capacitive heating devices (Thermotron RF-8) at seven institutions. Each institute was designated to treat specific organs. This paper contains the accumulations of the results obtained at different institutions charged for different tumours. Deep-seated tumours in the lung, stomach, pancreas, liver, urinary bladder and rectum were treated. A total of 177 cases examined from January 1985 to De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 11 publications
0
37
0
2
Order By: Relevance
“…Six out of 14 studies used a control population that enabled a comparison between treatments with and without hyperthermia [54,55,57,60,62,66]. In two studies, patients with a variety of carcinomas were included, but data were reported for the pancreatic patients separately [53,59].…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Six out of 14 studies used a control population that enabled a comparison between treatments with and without hyperthermia [54,55,57,60,62,66]. In two studies, patients with a variety of carcinomas were included, but data were reported for the pancreatic patients separately [53,59].…”
Section: Literature Searchmentioning
confidence: 99%
“…For the patients who received HT within the studies, this HT was in combination with radiotherapy for 17 patients (7%, two studies) [53,55], with chemoradiotherapy for 82 patients (33%, four studies) [54,60,62,66], and with chemotherapy for 149 patients (60%) in the remaining eight studies. Three types of hyperthermia treatment were applied: locoregional, whole-body and intraoperative hyperthermia.…”
Section: Patient Characteristics and Treatment Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…A key challenge prior to employing hyperthermia is to carry out in vitro assessment of the procedure's efficacy [4][5][6][7]. For our case, the goal is to assess fullerene agents to reduce heating time and improve hyperthermia efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The HY-deep 600WM V R (Verde Andromedic, Italy), Celsius TCS V R (Celsius 42þ, Cologne, Germany), Synchrotherm RF 1200 V R (Sychrotherm, Vigevano, Italy), and Thermotron RF-8 V R (Thermotron, MPR and Yamato, Japan) are capacitive hyperthermia systems which use electrodes to excite hyperthermia. In the past, the Thermotron RF-8 V R device has been used for treatment of invasive bladder carcinoma [19,20]. We do not discuss these systems further in this paper, since no recent clinical trials have been published regarding these hyperthermia systems in the treatment of bladder cancer.…”
Section: Capacitive Hyperthermia Systemsmentioning
confidence: 99%